1976
DOI: 10.1172/jci108521
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of plasma glucagon. Circulating components in normal subjects and patients with chronic renal failure.

Abstract: A B S T R A C T Plasma immunoreactive glucagon (IRG) concentrations were measured in 36 patients with chronic renal failure (CRF) and 32 normal subjects. In addition, the components of circulating IRG were analyzed by gel filtration in the fasting state and after physiological stimuli. Fasting IRG was elevated (P< 0.001) in CRF patients (534±32 pg/ml) compared with the levels found in healthy subjects (113±9 pg/ ml). Oral glucose suppressed plasma IRG in CRF patients from a basal level of 568+52 to a nadir of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(51 citation statements)
references
References 15 publications
3
48
0
Order By: Relevance
“…Plasma immunoreactive glucagon (IRG)' is elevated in uremia (1)(2)(3)(4)(5)(6)(7), and a significant portion of the glucagon immunoreactivity is present in a fraction with a mol wt of approximately 9,000 (4,6), consistent with descriptions of proglucagon (8)(9)(10)(11)(12)(13)(14). While changes in glucagon secretion do not appear to be responsible for the increments in total IRG (5,15), the pathogenesis of the alterations in the composition of the circulating hormone is not well understood.…”
Section: Introductionsupporting
confidence: 52%
See 3 more Smart Citations
“…Plasma immunoreactive glucagon (IRG)' is elevated in uremia (1)(2)(3)(4)(5)(6)(7), and a significant portion of the glucagon immunoreactivity is present in a fraction with a mol wt of approximately 9,000 (4,6), consistent with descriptions of proglucagon (8)(9)(10)(11)(12)(13)(14). While changes in glucagon secretion do not appear to be responsible for the increments in total IRG (5,15), the pathogenesis of the alterations in the composition of the circulating hormone is not well understood.…”
Section: Introductionsupporting
confidence: 52%
“…They do not appear to represent simple aggregates of the 3,500-mol wt material or noncovalent binding of this glucagon species to other plasma proteins. Exposure of these fractions to trypsin demonstrated that Peak A is resistant to the action of the enzyme, while the material in Peak B can be converted to immunoreactive fragments of smaller mol wt, some of which are similar in size to the native hormone (6). The latter observation lends support to the possibility that the 9,000-mol wt component might be a glucagon precursor.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Recent studies have pointed out that plasma glucagon immunoreactivity is heterogeneous (Valverde et al, 1970;Valverde et al, 1974;Weir et al, 1975;Valverde and Villanueva, 1976;Kuku et al, 1976;Jaspan et al, 1977) and has as many as four fractions when determined with antiserum 30K. There is at present little information regarding the immunoreactive nature of Big Plasma Glucagon (BPG) (Valverde et al, 1974) and 2000 mol.…”
Section: Endocrinolmentioning
confidence: 99%